ANALYSIS OF THE URGENCY OF USING DIGITAL LITERACY IN THE IMPLEMENTATION OF EDUCATION DURING A PANDEMIC IN SDN 106790 SEI MENCIRIM KAB.DELI SERDANG - Tisa Enika Br Sitepu (The International Conference on Education, Social Sciences and Technology (ICESST), 2022)
Along with increasingly rapid technological developments, the use of digital literacy in the implementation of education is very much needed, especially in the era of the Covid 19 pandemic which requires all parties involved in the learning process to be skilled in the use of facilities and various platforms that can facilitate all learning activities. Therefore, the urgency in using digital literacy during the educational period during this pandemic is a top priority and a necessity. The purpose of carrying out this literacy study is to determine the urgency of using digital literacy in the implementation of education during the pandemic at SDN 106780 Sei Mencirem. The method used is literature study. The steps taken are identifying, reviewing, evaluating, and interpreting all available research that is relevant with a study of the urgency of digital literacy in the implementation of online education. The results obtained are that digital literacy is needed and a priority that must be developed in education, especially during the pandemic of online-based education, digital literacy in education is no longer just important but has become a necessity.